Can body traits, other than wings, reflect the flight ability of Triatominae bugs? - María Laura Hernández; Jean Pierre Dujardin; David Eladio Gorla; Silvia Susana Catalá (Revista da Sociedade Brasileira de Medicina Tropical, 2015)
Abstract: INTRODUCTION : Insects of the subfamily Triatominae are vectors of Trypanosoma cruzi , the Chagas disease parasite, and their flying behavior has epidemiological importance. The flying capacity is strikingly different across and within Triatominae species, as well as between sexes or individuals. Many Triatoma infestans individuals have wings but no flying muscles. In other Triatominae species, no clear relationships were found between wing length and flying behavior. If wing presence or size is not reflective of the flying behavior, which other parts of the body could be considered as reliable markers of this important function? METHODS : The genus Mepraia has exceptional characteristics with invariably wingless females and wingless or winged males. We calculated the porous surface exposed to odorant molecules to estimate the olfactory capacity of Mepraia spinolai . The head shape and thorax size were estimated using the geometric morphometric approach and traditional morphometric techniques, respectively. RESULTS : Alary polymorphism in M. spinolai was significantly associated with consistent modification of the thorax size, head shape, and notable change in the estimated olfactory capacity. The macropterous individuals had a larger olfactory surface and thorax size and significantly different head shape compared to those of the micropterous individuals. CONCLUSIONS: We concluded that these structural changes could be associated with the flying potential of Triatominae. Thus, morphological attributes not found on wings could help determine the likely flying potential of the bugs.